Pengaruh Institutional Ownership, Dispersion of Wnership, Insider Ownership, dan Firm Size Terhadap Kebijakan Dividen Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Shofi Muniifah (Jurnal Manajemen Stratejik dan Simulasi Bisnis, 2021)
This study is aimed to determine the effect of Institutional Ownership, Dispersion of Ownership, Insider Ownership and Firm Size on Dividend Payout Ratio in Manufacturing Companies listed on the Indonesia Stock Exchange for the 2017-2019 period, amounting to 143 companies, as simultaneously and partially influence. As many as 33 samples of companies was taken using purposive sampling method. This research is an associative clause research and use secondary data for the type of data. Documentation is used for the data collection technique. Data analysis used multiple linear regression method. The results showed that Institutional Ownership partially positive and significant effect on Dividend Payout Ratio, Dispersion of Ownership partially positive and significant effect on Dividend Payout Ratio, Insider Ownership partially positive and significant effect on Dividend Payout Ratio, Firm Size partially positive and insignificant effect to Dividend Payout Ratio. Meanwhile, simultaneously Institutional Ownership, Dispersion of Ownership, Insider Ownership, and Firm Size simultaneously had a significant effect on the Dividend Payout Ratio. Keywords: Institutional Ownership, Dispersion of Ownership, Insider Ownership, Firm Size, and Dividend Payout Ratio.